Pit and Fissure Sealent Sebagai Pencegahan Karies Gigi Bagi Siswa Sekolah Dasar Negeri Kukuh Kecamatan Marga Tabanan Tahun 2018 - Asep Arifin Senjaya; I Nyoman Gejir; Ida Ayu Dewi Kumala Ratih; Ni Nyoman Dewi Supariani (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2019)
Indonesian Ministry of Health data (2013) showed 89% of children aged 12 years had dental caries, this is one proof that public awareness is still lacking in maintaining the health of their teeth and mouth. Residents who stated that they had problems with their teeth and mouth in the last 12 months in Tabanan Regency were 25.7%. This figure is above the Bali provincial figure of 24.0%. One of the preventive measures for dental caries is to seal (seal) pits and deep fissures on the surface of the tooth. Based on the preliminary interview with the Head of Kukuh Elementary School 1, 3 and 4 in Marga Sub-district, Tabanan Regency, it is known that there are no UKS or UKGS elementary schools. Based on the description above, a problem statement can be formulated: how to prevent dental caries for students in Kukuh District 1, 3 and 4 SDN in Marga Sub-district, Tabanan Regency in 2018? The service method is carried out with practice or direct action on the teeth of students of SDN 1,3, and 4 Kukuh, Marga District, Tabanan Regency. Based on the results and discussion, it can be suggested as follows: sealant action is carried out even earlier, to avoid carious teeth; if similar activities are carried out again, the community service team prepares tools and materials for dental fillings.Keywords: pit and fissure sealant, dental caries